Dye adsorbent by activated carbon - N. Selvanathan; Noor Syuhadah Subki; Muhammad Azwadi Sulaiman (Universiti Malaysia Kelantan, 2015)
Dyes are used extensively in many industries making the research on color production more important. Despite that, dyes are important class of pollutant in which it is disposed in water resources and causes major environmental problems due to toxicity and carcinogenic property of dye. However, the disposed dye into the environment can be treated by several alternatives. In this study, activated carbon derived from pineapple crown, core and peel were prepared by chemical activation using phosphoric acid (H3PO4). Laboratory prepared activated carbons were used to identify the suitability of its application to adsord methylene blue and malachite green. The results indicated that the activated carbon derived from pineapple crown shows maximum adsorption of methylene blue (38.6%) and malachite green. This study shows a benefit of transforming agriculture waste to value added product and also helps to solve over abundance pineapple waste problem